Dragon's merry Christmas - Pilkey, Dav, 1966- (New York, NY : Scholastic Inc., 2020)
"Dragon has a merry time in the Christmas season, decorating a tree outdoors, making a chocolate candy wreath, and sharing his Christmas gifts with those in need"-- Provided by publisher.
Originally published: New York : Orchard Books, 1991.
1.
1.
Accelerated Reader
Keywords: Dragon (Fictitious character : Pilkey) -- Juvenile fiction; Dragons -- Juvenile fiction; Christmas stories; Gifts -- Juvenile fiction; Sharing -- Juvenile fiction; Friendship -- Juvenile fiction; Dragon (Fictitious character : Pilkey) -- Fiction; Dragons -- Fiction; Christmas -- Fiction; Gifts -- Fiction; Sharing -- Fiction; Friendship -- Fiction; Picture books; Christmas fiction; Fantasy fiction; Readers (Publications)